The Influence of Psychological Contracts and Career Development on the Performance of State Civil Apparatus (ASN) Employees Moderated By Organizational Climate at University of Mataram - Agus Supratman; Santy Nururly; Dwi Putra Buana Sakti (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
This study aims to analyze the influence of psychological contracts, career development, and organizational climate on employee performance at the University of Mataram. Employee performance, in the context of state universities, is not only influenced by structural and administrative aspects, but also by psychological factors, human resource development, and perceptions of the work environment. This study used a quantitative approach with a survey method, where data was collected through questionnaires distributed to educational staff at the University of Mataram. Data analysis was conducted using inferential statistical analysis techniques to test the relationship and influence between research variables. The results showed that psychological contracts, career development, and organizational climate had a positive and significant influence on employee performance. A fulfilled psychological contract increased employee commitment and responsibility to the organization. Career development that is systematically and sustainably designed contributes to the increased competency and work productivity. Meanwhile, a conducive organizational climate, characterized by good communication, leadership support, and cooperation among employees, plays a crucial role in shaping positive work behavior. The findings of this study imply that the University of Mataram needs to strengthen its human resource management policies oriented toward fulfilment of psychological contracts, fair and transparent career development, and creation of a supportive organizational climate. These efforts are expected to improve employee performance sustainably and support the achievement of the institution's strategic goals.